1997
DOI: 10.1021/jm9701785
|View full text |Cite
|
Sign up to set email alerts
|

Antipsoriatic Anthrones with Modulated Redox Properties. 4. Synthesis and Biological Activity of Novel 9,10-Dihydro-1,8-dihydroxy-9-oxo-2- anthracenecarboxylic and -hydroxamic Acids

Abstract: A novel series of carboxylic and hydroxamic acids based on 1,8-dihydroxy-9(10H)-anthracenone were synthesized from 8-hydroxy-1-methoxy-9,10-anthracenedione as the key intermediate and evaluated both in the bovine polymorphonuclear leukocyte 5-lipoxygenase (5-LO) assay and in the HaCaT keratinocyte proliferation assay for their enzyme inhibitory and antiproliferative activity, respectively. The most potent inhibitors in both assays were the N-methylated hydroxamic acids 5d-8d with straight chain alkyl spacers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 52 publications
(122 reference statements)
0
19
0
Order By: Relevance
“…In psoriasis, NGF can have a pleiotropic role in the pathogenesis by regulating nerve growth, neuropeptides, angiogenesis, cell trafficking, and the function of T cells and mast cells, as recently reviewed (Raychaudhuri and Raychaudhuri, 2009). The HaCaT cell line has been widely used for the in vitro testing of antipsoriatic compounds (Muller and Prinz, 1997;Geilen et al, 1997). Therefore, in this study, we detail the mechanisms of neurotrophin-mediated induction of VEGF in HaCaT cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In psoriasis, NGF can have a pleiotropic role in the pathogenesis by regulating nerve growth, neuropeptides, angiogenesis, cell trafficking, and the function of T cells and mast cells, as recently reviewed (Raychaudhuri and Raychaudhuri, 2009). The HaCaT cell line has been widely used for the in vitro testing of antipsoriatic compounds (Muller and Prinz, 1997;Geilen et al, 1997). Therefore, in this study, we detail the mechanisms of neurotrophin-mediated induction of VEGF in HaCaT cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…HaCaTs are immortalized cell lines derived from keratinocytes in normal adult skin and the excessive proliferation of these keratinocytes results in psoriatic lesions (7). Therefore, HaCaT cells have been widely used as an in vitro model for the study of anti-psoriasis agents (8,9). …”
Section: Introductionmentioning
confidence: 99%
“…[4] The parent anthrone, namely 9A C H T U N G T R E N N U N G (10H)-anthracenone, has been classically used as a reagent for the analytical determination of sugars and many of its derivatives have interesting biological properties: antimicrobial, laxative, antipsoriatic or as telomerase inhibitors. [5] Recently, it has been found that some anthrone derivatives may display potent and selective antitumour activity. [6] Anthrone has been used as the diene component in Diels-Alder cycloadditions with a variety of dienophiles.…”
mentioning
confidence: 99%